The Effect of Local Revenue and General Allocation Fund on Capital Expenditure - Lupita Putri Yanti; Ramses Pakpahan (Yayasan Az Zukhruf Cendikia, 2024)
Purpose – This study aims to determine the effect of local revenue and general allocation funds on capital expenditure in the regencies and cities of Bali Province. Design/methodology/approach – The research employs a quantitative approach, analyzing annual reports from 8 regencies and 1 city in Bali Province from 2015 to 2020. The sample includes government financial data, and the study utilizes multiple regression analysis to test the hypotheses. The analysis is conducted using E-Views 9 software. Findings – The results indicate that local revenue (regional own-source revenue) has a positive and statistically significant effect on capital expenditure, meaning that higher local revenues lead to increased capital expenditure. In contrast, the general allocation fund has a negative but statistically insignificant effect on capital expenditure, suggesting that it does not significantly influence the level of capital spending. Research limitations/implications – The study is limited to a specific region (Bali Province) and time frame (2015-2020), which may affect the generalizability of the results to other regions or periods. Future research could expand the sample to include other provinces or longer periods to provide more comprehensive insights. Additionally, the findings imply that local governments may need to enhance their local revenue-generating capacities to boost capital expenditures.